An Experimental Study Of Natural Frequency Of Damaged Cable Net Supported Facade Panel - Ehsan, Nurul Syazwani Mohamad (Universiti Sains Malaysia, 2017)
Cable net supported facade system that has been widely used is a modern structure and has many advantages, such as pleasing aesthetics, easy constructability, efficient use of natural lighting and energy savings. It is commonly used in airport terminals, hotel lobbies, and trade centre. This research was conduct experimentally. The main focus for this research is to observe the natural frequency of damaged cable net structure. Three models were considered in this research. There were cable net only, cable net with perspex panels and cable net with perspex panel and silicone sealant. Besides that, this research was also carried out to observe the contribution and effect of perspex panel and silicone sealant to the cable net structure. In this research, the natural frequency of cable net supported facade panel was investigated via experiments and has been analyzed by using MATLAB 2015a software. The damaged cable in cable net system had caused the decreased in frequency of the cable net structure in the range of 1.40% to 2.06% but with the present of perspex panel and silicone sealant, the frequency was maintained around 70Hz. Although there was damaged in the cable, the perspex panels showed a significant effect to the natural frequency of the cable net structure. The frequency of the whole structure had increased in the range of 3.77% to 4.96%. The cable with 100% losses value in pre stress force represents the damaged cable in this study. Meanwhile, for the case of pre stress loss, the 30% losses value of the actual pre stress force showed a decrement of frequency in the range of 2.73 % to 4.07% and 60% losses value of actual pre stress showed a decrement of frequency in the range of 1.06% to 1.77%. The highest natural frequency recorded is produced by the cable net structure with perspex panel and silicone sealant with 77.25Hz.